Are level of education and employment related to symptoms of common mental disorders in current and retired professional footballers? - Gouttebarge, V.; Aoki, H.; Verhagen, E.; Kerkhoffs, G. (Asian Journal of Sports Medicine, 2016)
Background: Mental disorders have become a topic of increasing interest in research due to their serious consequences for quality of life and functioning..